Hubungan dukungan keluarga dengan motivasi lansia hipertensi dalam memeriksakan Tekanan darahnya - Sri Ayu Wulandhani; Sofiana - Nurchayati; Widia - Lestari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this research was to identify the correlation between family support and motivation of elderly with hypertention to control their blood pressure. The method of this research was a descriptive correlative with cross sectional approach. The sample in this research were 91 eldest with hypertention residing in the village of South Tangkerang with cluster sampling technique and stratified random sampling with 91 elderly which was selected based on inclusion criteria. The instrument was a questionnaire contains of 27 statement which had been tested the validity and reliability. The analysis used univariate and bivariate analysis by using Chi-squared test. The result showed that 50 respondent (54,9%) had possitive support and 49 respondent (53,8%) had high motivation. Chi-square test showed p value = 0,000 < (α = 0,05), it means that there is a correlation between family support and motivation of elderly with hypertention to control their blood pressure. Based on the result of this study, it recommended to family for caring the elderly to control their blood pressure in order to increase elderly’s biology, psychology, social, and spirituality. Keywords: elderly, family support, hypertention, motivation